Foamed material

JP7943772B2Active Publication Date: 2026-10-30NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022130618
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-18
Filing Date
2022-08-18
Publication Date
2026-10-30
Estimated Expiration
2042-08-18

Smart Images

  • Figure 0007943772000002
    Figure 0007943772000002
  • Figure 0007943772000003
    Figure 0007943772000003
  • Figure 0007943772000001
    Figure 0007943772000001
Patent Text Reader

Abstract

To provide a foam member comprising a resin foam and an adhesive layer, which has excellent integration between the resin foam and the adhesive layer and cleanliness.SOLUTION: There is provided a foam member which comprises a resin foam and an adhesive body disposed on at least one side of the resin foam, wherein the adhesive body comprises an adhesive layer and the resin foam has an average bubble diameter of 900 μm or less, the adhesive layer has a thickness of 50 μm or less and the total emission amount of toluene outgas and ethyl acetate outgas in the adhesive body is 8.0 μg / g or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a foamed material. [Background technology]

[0002] Foam materials are widely used as cushioning materials to protect screens, circuit boards, and electronic components in electronic devices. In recent years, with the trend towards thinner electronic devices, there has been a need to reduce the clearance in the areas where cushioning materials are placed. Furthermore, with the miniaturization and multi-functionality of electronic devices, the electronic components used are also tending to become smaller, sometimes requiring even thinner cushioning materials (foam materials).

[0003] The foamed components described above may be constructed by integrating the foam and the adhesive layer. The integration of the foam and the adhesive layer is important from the standpoint of enabling the foam to perform its intended function. For example, if the integration is poor (e.g., if the adhesion is poor), it may be necessary to press the foam and the adhesive layer together under high pressure during foamed component formation, which may impair the foam's intended function. In recent years, there has been a growing demand for foamed components that are environmentally friendly and have excellent cleanliness. Therefore, it is preferable that excellent integration of the foam and the adhesive layer be achieved without hindering cleanliness. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2017-186504 [Patent Document 2] Japanese Patent Publication No. 2015-034299 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] An object of the present invention is to provide a foam member comprising a resin foam and an adhesive layer, which is excellent in the integrity between the resin foam and the adhesive layer and in cleanliness. [Means for Solving the Problems]

[0006] The foam member of the present invention comprises a resin foam and an adhesive body disposed on at least one side of the resin foam, the adhesive body comprises an adhesive layer, the average cell diameter of the resin foam is 900 μm or less, the thickness of the adhesive layer is 50 μm or less, and the total emission amount of toluene outgas and ethyl acetate outgas in the adhesive body is 8.0 μg / g or less. In one embodiment, the adhesive body further comprises a base material, and the adhesive layer is disposed between the base material and the resin foam. In one embodiment, the adhesive body is an adhesive sheet. In one embodiment, the adhesive body comprises the adhesive layers disposed on both sides of the base material. In one embodiment, the base material is composed of polyethylene terephthalate. In one embodiment, the apparent density of the resin foam is 0.03 g / cm 3 to 0.4 g / cm 3 . In one embodiment, the coefficient of variation of the cell diameter of the resin foam is 0.4 or less. In one embodiment, the cell ratio of the resin foam is 97% or less. In one embodiment, the cell number density of the resin foam is 50 cells / mm 2 or more. In one embodiment, the resin foam comprises a polyolefin-based resin. In one embodiment, the polyolefin-based resin is a mixture of a polyolefin other than a polyolefin-based elastomer and a polyolefin-based elastomer. In one embodiment, the foam has a heat-melt layer on one side or both sides thereof. In one embodiment, the adhesive layer comprises a water-dispersible adhesive. In one embodiment, another adhesive layer is formed on the side of the resin foam opposite to the adhesive layer. [Effects of the Invention]

[0007] According to the present invention, it is possible to provide a foamed member comprising a resin foam and an adhesive layer, which exhibits excellent integrity between the resin foam and the adhesive layer, as well as superior cleanliness. [Brief explanation of the drawing]

[0008] [Figure 1] This is a schematic cross-sectional view of a foamed member according to one embodiment of the present invention. [Figure 2] This is a schematic cross-sectional view of a foamed member according to another embodiment of the present invention. [Modes for carrying out the invention]

[0009] A. Foamed material Figure 1 is a schematic cross-sectional view of a foamed member according to one embodiment of the present invention. The foamed member 100 comprises a resin foam 110 and an adhesive 120 disposed on at least one side of the resin foam 110.

[0010] The adhesive body 120 comprises an adhesive layer 121. As shown in Figure 1, the adhesive body 120 may consist only of the adhesive layer 121, or as shown in Figure 2, it may consist of a base material 122 and an adhesive layer 121. By arranging a base material, a foam member with high rigidity and excellent adhesion can be obtained. Furthermore, since adhesion is maintained even when each layer is made thin, further thinning is possible by using a base material. The adhesive layer may be arranged between the base material and the resin foam. Note that, as shown in Figure 2, if the adhesive body 120 comprises a base material 122, the adhesive layer 121 may be arranged on both sides of the base material 122. An adhesive body comprising a base material may be an adhesive sheet.

[0011] The above-mentioned resin foam has a cellular structure. Examples of cellular structures include closed-cell structures, open-cell structures, and semi-open-cell structures (a cellular structure in which closed-cell and open-cell structures are mixed). Preferably, the cellular structure of the resin foam is a semi-open-cell structure. Typically, the resin foam of the present invention is obtained by foaming a resin composition. The above-mentioned resin composition is a composition that contains at least the resin constituting the resin foam.

[0012] The average bubble diameter (average cell diameter) of the above-mentioned resin foam is 900 μm or less. Within this range, the anchoring force of the adhesive layer to the resin foam is high, and a foamed material with excellent integration between the resin foam and the adhesive layer can be obtained. With such a foamed material, the bonding of the resin foam and the adhesive layer during lamination can be performed at low pressure during manufacturing. As a result, a foamed material can be obtained in which the functions of the resin foam can be favorably exhibited. Furthermore, a foamed material with excellent integration between the resin foam and the adhesive layer is also advantageous in that it can help prevent misalignment when the foamed material is punched out and individualized. The method for measuring the average bubble diameter will be described later.

[0013] The thickness of the adhesive layer is 50 μm or less. Within this range, a thin foamed material can be obtained. The foamed material of the present invention is suitable for use in areas with narrow clearances. Furthermore, if the thickness of the adhesive layer is within the above range, a foamed material with excellent cleanliness and punchability can be obtained.

[0014] Although not shown in the diagram, another adhesive layer may be formed on the side of the resin foam opposite to the adhesive layer.

[0015] In the above adhesive, the total amount of toluene outgassing and ethyl acetate outgassing is 8.0 μg / g or less. The foamed member of the present invention is advantageous in that it has low outgassing, i.e., high cleanliness. As described above, obtaining a foamed member that is thin, has excellent integration between the resin foam and the adhesive (adhesive layer), and also has excellent cleanliness is one of the major achievements of the present invention. The total amount of toluene outgassing and ethyl acetate outgassing is the amount of outgassing that occurs when only the adhesive is left at 80°C for 30 minutes. The specific measurement method will be described later. The weight of the adhesive that serves as the measurement standard for the total amount of toluene outgassing and ethyl acetate outgassing is the sum of the weight of the adhesive layer and the weight of the substrate which is placed as needed. A foamed member with low toluene outgassing and ethyl acetate outgassing can be obtained, for example, by using a water-dispersible adhesive (described later) as the adhesive constituting the adhesive layer.

[0016] The above foam material contains 1000 g / cm³ 2 The thickness recovery rate (hereinafter also referred to as the instantaneous recovery rate) after being maintained for 120 seconds under the applied load is preferably 55% or more, more preferably 60% or more, even more preferably 70% or more, even more preferably 80% or more, even more preferably 85% or more, and particularly preferably 90% or more. Foamed materials with an instantaneous recovery rate in this range exhibit desirable behavior, such as small changes in shape, including thickness, when punched out, and recovering quickly even if the thickness is temporarily reduced by punching, thus having excellent punchability. A higher instantaneous recovery rate is preferable, but its upper limit is, for example, 99% (preferably 100%). The method for measuring the instantaneous recovery rate will be described later.

[0017] B. Resin foam As described above, the average cell diameter (average cell size) of the resin foam is 900 μm or less. The average cell diameter (average cell size) of the resin foam is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, and particularly preferably 80 μm or less. Further, the average cell diameter (average cell size) of the resin foam is preferably 10 μm or more, even more preferably 20 μm or more, and still more preferably 40 μm or more. When the average cell diameter (average cell size) is within the above range, a foam member can be obtained that has high anchoring force of the pressure-sensitive adhesive body (pressure-sensitive adhesive layer) to the resin foam, and exhibits excellent integrity between the resin foam and the pressure-sensitive adhesive body (pressure-sensitive adhesive layer). In addition, a resin foam that is more excellent in flexibility and stress dispersibility can be obtained. Furthermore, a resin foam that is also excellent in compression recovery property, punching processability, and resistance to repeated impacts can be obtained.

[0018] The 50% compression load of the above resin foam is preferably 30 N / cm 2 or less, more preferably 10 N / cm 2 or less, even more preferably 8 N / cm 2 or less, particularly preferably 5 N / cm 2 or less, and most preferably 3 N / cm 2 or less. Within such a range, a foam member that preferably has flexibility and is excellent in punching processability can be obtained. The lower limit of the 50% compression load of the resin foam is, for example, 0.5 N / cm 2 . The 50% compression load of the resin foam refers to the stress (N) when compressed to a compression ratio of 50%, converted per unit area (1 cm 2 ).

[0019] The cell number density of the above resin foam is preferably 50 cells / mm 2 or more, more preferably 65 cells / mm 2 or more, even more preferably 80 cells / mm 2 or more, still more preferably 90 cells / mm 2 or more, further preferably 100 cells / mm 2 or more, and particularly preferably 110 cells / mm2 The above is the most preferred value, with 120 pieces / mm² being the most preferable. 2 The above is the case. Within this range, the bonding area between the resin foam and the adhesive (adhesive layer) increases, and a foamed member with excellent integration between the resin foam and the adhesive (adhesive layer) can be obtained. Furthermore, a foamed member that is preferably flexible and has excellent die-cutting processability can be obtained. In addition, the higher the number density of bubbles, the easier it is to store energy when compressed, and a resin foam with excellent compression recovery force can be obtained. A foamed member having such a resin foam has excellent die-cutting processability. The upper limit of the number density of bubbles in the resin foam is preferably 400 bubbles / mm 2 More preferably, 350 pieces / mm 2 And more preferably, 300 pieces / mm 2 And more preferably 250 pieces / mm 2 And, particularly preferably, 200 pieces / mm 2 The number density of bubbles in a resin foam is the number density of bubbles observed in a randomly selected cross-section of the resin foam, and can be determined by image analysis of the cross-section of the resin foam.

[0020] The apparent density of the resin foam is preferably 0.4 g / cm³. 3 The following, and more preferably 0.3 g / cm³ 3 The following applies. Furthermore, the apparent density of the resin foam is preferably 0.01 g / cm³. 3 The above is more preferable, or 0.03 g / cm³. 3 This concludes the explanation. If the apparent density is within the above range, a foamed material with excellent integration between the resin foam and the adhesive (adhesive layer) can be obtained. Furthermore, a resin foam with excellent die-cutting properties, flexibility, and stress distribution can be obtained. Foaming properties can be determined by the apparent density. In one embodiment, the apparent density of the resin foam is preferably 0.1 g / cm³. 3 The following, and more preferably 0.08 g / cm³ 3 The following, and more preferably 0.06 g / cm³ 3 The following applies: In another embodiment, the apparent density of the resin foam is preferably 0.08 g / cm³. 3The above is true, and more preferably 0.1 g / cm³ 3 The above is preferable, and more preferably 0.15 g / cm³ 3 That concludes the explanation. The method for measuring apparent density will be described later.

[0021] The thickness of the resin foam is preferably 100 μm or more, more preferably 150 μm or more, even more preferably 200 μm or more, even more preferably 300 μm or more, even more preferably 400 μm or more, and particularly preferably 500 μm or more. The upper limit of the thickness of the resin foam is preferably 8000 μm or less, more preferably 5000 μm or less, even more preferably 4000 μm or less, even more preferably 3000 μm or less, and particularly preferably 2000 μm or less. Within this range, a fine and uniform cellular structure can be formed, which is advantageous in that it can exhibit excellent punching processability and shock absorption.

[0022] The coefficient of variation of the cell diameter (bubble diameter) of the resin foam described above is preferably 0.4 or less, more preferably 0.35 or less, even more preferably 0.3 or less, particularly preferably 0.25 or less, and most preferably 0.2 or less. Within this range, a foamed member with excellent integration between the resin foam and the adhesive (adhesive layer) can be obtained. Furthermore, when compressive force is applied by punching or the like, the variation in bubble deformation is reduced. With such a resin foam, for example, when punched, a processed product (cut product) with excellent thickness accuracy can be obtained. Also, if the coefficient of variation of the cell diameter is within the above range, deformation due to impact becomes uniform, localized stress loading is prevented, excellent stress distribution is obtained, and a foamed member with particularly excellent impact resistance can be obtained. The smaller the coefficient of variation, the better, but the lower limit is, for example, 0.15 (preferably 0.1, more preferably 0.01). The method for measuring the coefficient of variation of the cell diameter will be described later.

[0023] The cell content of the resin foam described above is preferably 97% or less, and more preferably 95% or less. In one embodiment, the cell content of the resin foam is 90% or less (preferably 85% or less, more preferably 78% or less, and even more preferably 75% or less). Within this range, a resin foam with a small change in thickness when the resin foam and adhesive are pressed together can be obtained. The cell content of the resin foam described above is preferably 30% or more, more preferably 50% or more, and even more preferably 60% or more. Within this range, a resin foam with appropriate flexibility can be obtained. Such a resin foam has excellent die-cutting properties and prevents the occurrence of uncut pieces when die-cutting.

[0024] The rate of change in thickness of the resin foam during compression is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, particularly preferably 2% or less, and most preferably 1% or less. Within this range, a foam member with good recovery properties and excellent die-cutting processability can be obtained. In this specification, the "rate of change in thickness of the resin foam during compression" is the rate of change in thickness when the resin foam and adhesive are laminated, compressed and bonded by three passes of a 5kg roller, and then left for 30 minutes, and is calculated using the following formula. The percentage change in thickness during crimping [%] = (thickness before crimping - thickness after crimping) / (thickness before crimping) × 100

[0025] The thickness of the cell walls of the resin foam described above is preferably 0.1 μm to 10 μm, more preferably 0.3 μm to 8 μm, even more preferably 0.5 μm to 5 μm, particularly preferably 0.7 μm to 4 μm, and most preferably 1 μm to 3 μm. Within this range, a resin foam with appropriate strength can be obtained. Such a resin foam has excellent die-cutting properties, preventing tearing, dust generation, and uncut pieces during die-cutting. Furthermore, if the cell wall thickness is within the above range, a resin foam with superior flexibility and stress distribution can be obtained. The cell wall thickness can be measured by capturing an enlarged image of the cell portion of the resin foam and performing image analysis using the analysis software of the measuring instrument.

[0026] When the cell structure of the resin foam described above is a semi-continuous semi-closed cell structure, the proportion of closed cell structures is preferably 40% or less, and more preferably 30% or less. In this specification, the proportion of closed cell structures in the resin foam is determined, for example, by immersing the object to be measured in water in an environment of 23°C and 50% humidity, measuring the mass thereafter, and then measuring the mass again after thoroughly drying it in an oven at 80°C. Alternatively, since open cells can retain moisture, the mass portion of the open cell structure can be measured and determined accordingly.

[0027] The impact absorption of the above resin foam is preferably 20% or more, more preferably 27% or more, even more preferably 30% or more, particularly preferably 35% or more, and most preferably 40% or more. The impact absorption is measured as follows. A test specimen is formed by arranging resin foam, double-sided tape (product number: No. 5603W, manufactured by Nitto Denko), and PET film (product number: Diafoil MRF75, manufactured by Mitsubishi Plastics) in that order on an impact force sensor. A 66g steel ball is dropped onto the test specimen from a height of 50cm above the PET film, and the impact force F1 is measured. Furthermore, the impact force F0 of the blank is measured by dropping the steel ball directly onto the impact force sensor as described above. The impact absorption (%) is calculated from F1 and F0 using the formula (F0-F1) / F0×100.

[0028] The shape of the above-mentioned resin foam can be any appropriate shape depending on the purpose. A typical example of such a shape is a sheet.

[0029] The above-mentioned resin foam may have a heat-melt layer on one or both sides. A resin foam having a heat-melt layer can be obtained, for example, by rolling the resin foam (or a precursor (foamed structure) of the resin foam) using a pair of heated rolls heated to a temperature above the melting temperature of the resin composition constituting the resin foam. Forming a resin foam having a heat-melt layer increases the bonding area between the resin foam and the adhesive (adhesive layer), improving the adhesion between the resin foam and the adhesive (adhesive layer), and resulting in a foamed member with excellent integration of these layers.

[0030] The bubble rate (cell rate) of the fused layer is preferably 30% or less, more preferably 20% or less, even more preferably 10% or less, particularly preferably 5% or less, and most preferably 0%. The thickness of the fused layer is preferably 0.15 mm to 0.05 mm, more preferably 0.13 mm to 0.07 mm, and even more preferably 0.11 mm to 0.09 mm.

[0031] (Method for forming resin foam) The above-mentioned resin foam can be formed by any suitable method, provided that the effects of the present invention are not impaired. Typical such methods include foaming a resin composition containing a resin material (polymer). The resin composition contains any suitable resin material (polymer).

[0032] Examples of the polymers mentioned above include acrylic resins, silicone resins, urethane resins, polyolefin resins, ester resins, and rubber resins. These polymers may be used individually or in combination of two or more types.

[0033] The polymer content is preferably 30 to 95 parts by weight, more preferably 35 to 90 parts by weight, even more preferably 40 to 80 parts by weight, and particularly preferably 40 to 60 parts by weight, per 100 parts by weight of the resin composition. Within this range, a resin foam with superior flexibility and stress dispersion can be obtained.

[0034] In one embodiment, a polyolefin resin is used as the polymer.

[0035] The content of the polyolefin resin is preferably 50 to 100 parts by weight, more preferably 70 to 100 parts by weight, even more preferably 90 to 100 parts by weight, particularly preferably 95 to 100 parts by weight, and most preferably 100 parts by weight, relative to 100 parts by weight of the above polymer.

[0036] Preferably, the polyolefin resin is at least one selected from the group consisting of polyolefins and polyolefin-based elastomers, and more preferably, polyolefins and polyolefin-based elastomers are used in combination. Polyolefins and polyolefin-based elastomers may be used individually or in combination of two or more. In this specification, the term "polyolefin" does not include "polyolefin-based elastomers."

[0037] When polyolefin and polyolefin-based elastomer are used in combination as the polyolefin-based resin, the weight ratio of polyolefin to polyolefin-based elastomer (polyolefin / polyolefin-based elastomer) is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 90 / 10, even more preferably 20 / 80 to 80 / 20, and particularly preferably 30 / 70 to 70 / 30. In one embodiment, the weight ratio of polyolefin to polyolefin-based elastomer (polyolefin / polyolefin-based elastomer) is preferably 25 / 75 to 75 / 25, and more preferably 35 / 65 to 65 / 35. Within this range, a resin foam can be obtained that has excellent compression recovery, suppresses shape changes (especially thickness changes) before and after die-cutting, has appropriate strength, and has excellent die-cutting processability.

[0038] As the polyolefin, any suitable polyolefin can be used as long as it does not impair the effects of the present invention. Examples of such polyolefins include linear polyolefins and branched (having branched) polyolefins. In one embodiment, a branched polyolefin is used as the polyolefin resin. In this embodiment, only a branched polyolefin may be used as the polyolefin, or a combination of a branched polyolefin and a linear polyolefin may be used. By using a branched polyolefin, a resin foam with a small average bubble diameter and excellent impact resistance can be obtained. The content ratio of the branched polyolefin is preferably 30 to 100 parts by weight, and more preferably 50 to 80 parts by weight, per 100 parts by weight of polyolefin.

[0039] Examples of the polyolefins mentioned above include polymers containing structural units derived from α-olefins. The polyolefin may consist solely of structural units derived from α-olefins, or it may consist of structural units derived from α-olefins and structural units derived from monomers other than α-olefins. When the polyolefin is a copolymer, any suitable copolymerization form can be adopted. Examples include random copolymers and block copolymers.

[0040] As α-olefins that can constitute polyolefins, for example, α-olefins having 2 to 8 carbon atoms (preferably 2 to 6, more preferably 2 to 4) (e.g., ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, etc.) are preferred. There may be only one α-olefin or two or more α-olefins.

[0041] Examples of monomers other than α-olefins that constitute polyolefins include ethylenically unsaturated monomers such as vinyl acetate, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, and vinyl alcohol. There may be only one monomer other than α-olefin, or there may be two or more monomers.

[0042] Examples of polyolefins include, for example, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene (propylene homopolymer), copolymers of ethylene and propylene, copolymers of ethylene and α-olefins other than ethylene, copolymers of propylene and α-olefins other than propylene, copolymers of ethylene, propylene, and α-olefins other than ethylene and propylene, and copolymers of propylene and ethylenically unsaturated monomers.

[0043] In one embodiment, a polypropylene polymer having propylene-derived structural units is used as the polyolefin. Examples of polypropylene polymers include polypropylene (propylene homopolymer), copolymers of ethylene and propylene, and copolymers of propylene and α-olefins other than propylene, with polypropylene (propylene homopolymer) being preferred. The polypropylene polymer may be used alone or in combination of two or more types.

[0044] The melt flow rate (MFR) of the polyolefin at a temperature of 230°C is preferably 0.25 g / 10 min to 10 g / 10 min, more preferably 0.3 g / 10 min to 6 g / 10 min, even more preferably 0.35 g / 10 min to 5 g / 10 min, particularly preferably 0.35 g / 10 min to 1 g / 10 min, and most preferably 0.35 g / 10 min to 0.6 g / 10 min, in order to better express the effects of the present invention. In this specification, the above melt flow rate (MFR) refers to the MFR measured at a temperature of 230°C and a load of 2.16 kgf (21.2 N) based on ISO 1133 (JIS-K-7210). In one embodiment, the die swell ratio and shear viscosity of the resin are controlled by the melt flow rate of the polyolefin constituting the resin foam.

[0045] The weight-average molecular weight of the polyolefin is preferably 50,000 to 120,000, more preferably 55,000 to 110,000, and even more preferably 60,000 to 100,000. Within this range, the die swell ratio and shear viscosity of the resin can be favorably adjusted. The molecular weight distribution (weight-average molecular weight / number-average molecular weight) of the polyolefin is preferably 7 to 10, more preferably 6 to 9. Within this range, the die swell ratio and shear viscosity of the resin can be favorably adjusted. The weight-average molecular weight and number-average molecular weight can be determined by gel permeation chromatography (solvent: tetrahydrofuran, polystyrene equivalent).

[0046] As for the polyolefin, commercially available products may be used, such as "E110G" (manufactured by Prime Polymer Co., Ltd.), "EA9" (manufactured by Nippon Polypropylene Co., Ltd.), "EA9FT" (manufactured by Nippon Polypropylene Co., Ltd.), "E-185G" (manufactured by Prime Polymer Co., Ltd.), "WB140HMS" (manufactured by Borealis), and "WB135HMS" (manufactured by Borealis).

[0047] As the polyolefin elastomer, any suitable polyolefin elastomer can be used as long as it does not impair the effects of the present invention. Examples of such polyolefin elastomers include so-called non-crosslinked thermoplastic olefin elastomers (TPO), such as ethylene-propylene copolymer, ethylene-propylene-diene copolymer, ethylene-vinyl acetate copolymer, polybutene, polyisobutylene, chlorinated polyethylene, elastomers in which polyolefin components and rubber components are physically dispersed, and elastomers having a structure in which polyolefin components and rubber components are microphase separated; and dynamically crosslinked thermoplastic olefin elastomers (TPV), which are multiphase polymers obtained by dynamically heat-treating a mixture containing a resin component A (olefin resin component A) that forms a matrix and a rubber component B that forms domains in the presence of a crosslinking agent, and having a sea-island structure in which crosslinked rubber particles are finely dispersed as domains (island phases) in the resin component A which is the matrix (sea phase).

[0048] The polyolefin elastomer preferably contains a rubber component. Examples of such rubber components are those described in Japanese Patent Publication No. 08-302111, Japanese Patent Publication No. 2010-241934, Japanese Patent Publication No. 2008-024882, Japanese Patent Publication No. 2000-007858, Japanese Patent Publication No. 2006-052277, Japanese Patent Publication No. 2012-072306, Japanese Patent Publication No. 2012-057068, Japanese Patent Publication No. 2010-241897, Japanese Patent Publication No. 2009-067969, and Japanese Patent Publication No. 03 / 002654.

[0049] Elastomers having a structure in which the polyolefin component and the olefin-based rubber component are microphase separated include, specifically, elastomers composed of polypropylene resin (PP) and ethylene-propylene rubber (EPM), and elastomers composed of polypropylene resin (PP) and ethylene-propylene-diene rubber (EPDM). The weight ratio of the polyolefin component to the olefin-based rubber component (polyolefin component / olefin-based rubber) is preferably 90 / 10 to 10 / 90, and more preferably 80 / 20 to 20 / 80.

[0050] Dynamically crosslinked thermoplastic olefin elastomers (TPVs) generally have a higher elastic modulus and lower compression set than non-crosslinked thermoplastic olefin elastomers (TPOs). This results in good recovery properties, and when used in resin foams, they can exhibit excellent resilience.

[0051] Dynamically crosslinked thermoplastic olefin elastomers (TPVs), as described above, are obtained by dynamically heat-treating a mixture containing a resin component A (olefin resin component A) that forms the matrix and a rubber component B that forms the domains, in the presence of a crosslinking agent. They are multiphase polymers having a sea-island structure in which crosslinked rubber particles are finely dispersed as domains (island phases) in the resin component A, which is the matrix (sea phase).

[0052] Examples of dynamically crosslinked thermoplastic olefin elastomers (TPVs) include those described in Japanese Patent Publication No. 2000-007858, Japanese Patent Publication No. 2006-052277, Japanese Patent Publication No. 2012-072306, Japanese Patent Publication No. 2012-057068, Japanese Patent Publication No. 2010-241897, Japanese Patent Publication No. 2009-067969, and Table 03 / 002654, etc.

[0053] As the dynamically crosslinked thermoplastic olefin elastomer (TPV), commercially available products may be used, such as "Zeotherm" (manufactured by Nippon Zeon Co., Ltd.), "Thermoran" (manufactured by Mitsubishi Chemical Corporation), and "Sarlink 3245D" (manufactured by Toyobo Co., Ltd.).

[0054] The melt flow rate (MFR) of the polyolefin elastomer at a temperature of 230°C is preferably 1.5 g / 10 min to 25 g / 10 min, more preferably 2 g / 10 min to 20 g / 10 min, and even more preferably 2 g / 10 min to 15 g / 10 min.

[0055] In one embodiment, two or more polyolefin elastomers having different melt flow rates (MFRs) at 230°C within the above range are used in combination. In this case, a polyolefin elastomer (low-MFR polyolefin elastomer) having a melt flow rate (MFR) at 230°C preferably between 1.5 g / 10 min and less than 8 g / 10 min (more preferably 2 g / 10 min to 5 g / 10 min) and a polyolefin elastomer (high-MFR polyolefin elastomer) having a melt flow rate (MFR) at 230°C preferably between 8 g / 10 min and 25 g / 10 min (more preferably 9 g / 10 min to 20 g / 10 min, and even more preferably 10 g / 10 min to 20 g / 10 min) can be used in combination. In this way, the melt tension of the polyolefin elastomer is preferably adjusted, and as a result, the effects of the present invention become more pronounced.

[0056] The blending ratio of the low-MFR polyolefin elastomer to the high-MFR polyolefin elastomer (low-MFR polyolefin elastomer / high-MFR polyolefin elastomer; weight ratio) is preferably 1.5 to 5, more preferably 1.8 to 3.5, and particularly preferably 2 to 3. Within this range, the melt tension of the polyolefin elastomer is nicely adjusted, and as a result, the effects of the present invention become remarkable.

[0057] The melt tension (at 190°C, at break) of the polyolefin elastomer is preferably less than 10 cN, and more preferably 5 cN to 9.5 cN. In one embodiment, the die swell ratio and shear viscosity of the resin are controlled by the melt tension of the polyolefin elastomer constituting the resin foam.

[0058] The JIS A hardness of polyolefin elastomers is preferably 30° to 95°, more preferably 35° to 90°, even more preferably 40° to 88°, particularly preferably 45° to 85°, and most preferably 50° to 83°. Note that JIS A hardness is measured according to ISO 7619 (JIS K6253).

[0059] In one embodiment, the resin foam (i.e., the resin composition) may further contain a filler. By including a filler, it is possible to form a resin foam that requires a large amount of energy to deform the cell walls, and this resin foam exhibits excellent shock absorption. Furthermore, including a filler is advantageous because it allows for the formation of a fine and uniform cell structure, which can also result in excellent shock absorption. The filler may be used alone or in combination of two or more types.

[0060] The content ratio of the above-mentioned filler is preferably 10 to 150 parts by weight, more preferably 30 to 130 parts by weight, and even more preferably 50 to 100 parts by weight, relative to 100 parts by weight of the polymer constituting the resin foam. Within this range, the above-mentioned effect becomes significant.

[0061] In one embodiment, the filler is inorganic. Examples of materials that constitute the inorganic filler include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whiskers, silicon nitride, boron nitride, crystalline silica, amorphous silica, metals (e.g., gold, silver, copper, aluminum, nickel), carbon, graphite, and the like.

[0062] In one embodiment, the filler is an organic material. Examples of materials that constitute the organic filler include polymethyl methacrylate (PMMA), polyimide, polyamideimide, polyether ether ketone, polyetherimide, polyesterimide, and the like.

[0063] A flame retardant may be used as the filler material. Examples of flame retardants include bromine-based flame retardants, chlorine-based flame retardants, phosphorus-based flame retardants, and antimony-based flame retardants. Preferably, from the viewpoint of safety, a non-halogen-non-antimony flame retardant is used.

[0064] Examples of non-halogen-non-antimony flame retardants include compounds containing aluminum, magnesium, calcium, nickel, cobalt, tin, zinc, copper, iron, titanium, boron, etc. Examples of such compounds (inorganic compounds) include hydrated metal compounds such as aluminum hydroxide, magnesium hydroxide, magnesium oxide-nickel oxide hydrate, and magnesium oxide-zinc oxide hydrate.

[0065] The above-mentioned filler may be subjected to any appropriate surface treatment. Examples of surface treatments include silane coupling treatment and stearic acid treatment.

[0066] The bulk density of the above-mentioned filler is preferably 0.8 g / cm³. 3 The following, and more preferably 0.6 g / cm³ 3 The following, and more preferably 0.4 g / cm³ 3 The following, and particularly preferably 0.3 g / cm³ 3 The following applies. Within this range, the filler can be incorporated with good dispersibility, and the effect of adding the filler can be fully realized even with a low filler content. Resin foams with a low filler content are advantageous in that they are highly foamed, flexible, and have excellent stress distribution and appearance. The lower limit of the bulk density of the filler is, for example, 0.01 g / cm³. 3 The concentration is preferably 0.05 g / cm³. 3 More preferably 0.1 g / cm³3 That is the case.

[0067] The number-average particle diameter (primary particle diameter) of the filler is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. Within this range, the filler can be contained with good dispersibility and a uniform buoyancy structure can be formed. As a result, a resin foam with excellent stress dispersion and appearance can be obtained. The lower limit of the number-average particle diameter of the filler is, for example, 0.1 μm. The number-average particle diameter of the filler can be measured using a particle size analyzer (Micrtrac II, Microtrac-Bell Co., Ltd.) with a suspension prepared by mixing 1 g of filler with 100 g of water as a sample.

[0068] The specific surface area of ​​the above-mentioned filler is preferably 2 m². 2 / g or more, more preferably 4m 2 / g or more, and more preferably 6m 2 The value is 1 / g or more. Within this range, the filler can be incorporated with good dispersibility and a uniform cellular structure can be formed. As a result, a resin foam with excellent stress dispersion and appearance can be obtained. The upper limit of the specific surface area of ​​the filler is, for example, 20 m². 2 The value is / g. The specific surface area of ​​the filler can be measured by the BET method, that is, by adsorbing molecules with a known adsorption area onto the filler surface under low temperature conditions using liquid nitrogen, and then measuring the amount of adsorption.

[0069] The resin composition may contain any other suitable components, as long as they do not impair the effects of the present invention. Such other components may be one or more. Examples of such other components include rubber, resins other than the polymer blended as the resin material, softeners, aliphatic compounds, anti-aging agents, antioxidants, light stabilizers, weathering agents, UV absorbers, dispersants, plasticizers, carbon, antistatic agents, surfactants, crosslinking agents, thickeners, rust inhibitors, silicone compounds, tension modifiers, shrinkage inhibitors, flow modifiers, gelling agents, curing agents, reinforcing agents, foaming agents, foaming nucleators, colorants (pigments, dyes, etc.), pH adjusters, solvents (organic solvents), thermal polymerization initiators, photopolymerization initiators, lubricants, crystal nucleating agents, crystallization accelerators, vulcanizing agents, surface treatment agents, and dispersion aids.

[0070] As described above, resin foams are typically obtained by foaming a resin composition. Methods commonly used in foam molding, such as physical or chemical methods, can be employed for foaming (how to form bubbles). That is, resin foams may typically be foams formed by physical methods (physical foams) or foams formed by chemical methods (chemical foams). Physical methods generally involve dispersing gaseous components such as air or nitrogen in a polymer solution and forming bubbles through mechanical mixing (mechanical foams). Chemical methods generally involve forming cells with gases produced by the thermal decomposition of a foaming agent added to a polymer base, thereby obtaining a foam.

[0071] The resin composition to be subjected to foam molding may be prepared, for example, by mixing its constituent components using any suitable melt-kneading apparatus, such as an open-type mixing roll, a closed-type Banbury mixer, a single-screw extruder, a twin-screw extruder, a continuous kneader, or a pressure kneader.

[0072] Embodiment 1 for forming resin foam One embodiment 1 for forming a resin foam is a method in which a resin foam is formed by mechanically foaming an emulsion resin composition (an emulsion containing a resin material (polymer), etc.) through a step (step A). ​​Examples of foaming devices include high-speed shear type devices, vibration type devices, and pressurized gas discharge type devices. Among these foaming devices, a high-speed shear type device is preferred from the viewpoint of miniaturizing the bubble diameter and producing large volumes. This embodiment 1 for forming a resin foam is applicable to formation from any resin composition.

[0073] A higher solid content concentration in the emulsion is preferable from the viewpoint of film-forming properties. The solid content concentration of the emulsion is preferably 30% by weight or more, more preferably 40% by weight or more, and even more preferably 50% by weight or more.

[0074] The bubbles generated by mechanical stirring are formed when gas is incorporated into the emulsion. Any suitable gas can be used as the gas, as long as it is inert to the emulsion and does not impair the effects of the present invention. Examples of such gases include air, nitrogen, and carbon dioxide.

[0075] The foamed emulsion resin composition (bubble-containing emulsion resin composition) foamed by the above method can be applied to a substrate and dried in a step (step B) to obtain the foamed resin of the present invention. Examples of substrates include peel-treated plastic films (such as peel-treated polyethylene terephthalate films) and plastic films (such as polyethylene terephthalate films).

[0076] In step B, any suitable coating method and drying method can be adopted as long as they do not impair the effects of the present invention. Preferably, step B includes a pre-drying step B1 in which the bubble-containing emulsion resin composition applied to the substrate is dried at 50°C or higher and less than 125°C, and a main drying step B2 in which it is then dried further at 125°C or higher and 200°C or lower.

[0077] By providing a pre-drying step B1 and a main drying step B2, it is possible to prevent the coalescence and bursting of bubbles due to a rapid rise in temperature. In particular, with thin foam sheets, bubbles coalesce and burst due to a rapid rise in temperature, so providing a pre-drying step B1 is highly significant. The temperature in the pre-drying step B1 is preferably 50°C to 100°C. The duration of the pre-drying step B1 is preferably 0.5 minutes to 30 minutes, and more preferably 1 minute to 15 minutes. The temperature in the main drying step B2 is preferably 130°C to 180°C or lower, and more preferably 130°C to 160°C. The duration of the main drying step B2 is preferably 0.5 minutes to 30 minutes, and more preferably 1 minute to 15 minutes.

[0078] Embodiment 2 for forming resin foam One embodiment 2 for forming a resin foam is a method in which a resin composition is foamed with a foaming agent to form a foam. As the foaming agent, one that is normally used in foam molding can be used, and from the viewpoint of environmental protection and low contamination of the foamed material, it is preferable to use a high-pressure inert gas.

[0079] Any suitable inert gas can be used as the inert gas, as long as it is inert to the resin composition and can impregnate it. Examples of such inert gases include carbon dioxide, nitrogen gas, and air. These gases may be used in mixtures. Of these, carbon dioxide is preferred from the viewpoint of impregnating the resin material (polymer) in large quantities and having a fast impregnation rate.

[0080] The inert gas is preferably in a supercritical state. In particular, it is especially preferable to use supercritical carbon dioxide. In a supercritical state, the solubility of the inert gas in the resin composition is increased, allowing for high concentrations of inert gas to be incorporated. Furthermore, because the concentration of the inert gas becomes high during a rapid pressure drop, more bubble nuclei are generated. The density of the bubbles formed by the growth of these nuclei is higher than in other states, even if the porosity is the same, thus enabling the production of fine bubbles. The critical temperature of carbon dioxide is 31°C and the critical pressure is 7.4 MPa.

[0081] Methods for forming a foam by impregnating a resin composition with a high-pressure inert gas include, for example, a gas impregnation step in which an inert gas is impregnated under high pressure into a resin composition containing a resin material (polymer), a depressurization step in which the pressure is reduced after the gas impregnation step to foam the resin material (polymer), and a heating step in which bubbles are grown by heating as needed. In this case, a pre-molded unfoamed molded body may be impregnated with the inert gas, or a molten resin composition may be impregnated with an inert gas under pressure and then molded under depressurization. These steps may be carried out in either a batch or continuous manner. That is, the resin composition may be pre-molded into an appropriate shape such as a sheet to form an unfoamed resin molded body, and then this unfoamed resin molded body may be impregnated with a high-pressure gas and foamed by releasing the pressure in a batch manner, or the resin composition may be kneaded with a high-pressure gas under pressure, molded and foamed simultaneously by releasing the pressure in a continuous manner.

[0082] An example of manufacturing foam using a batch method is shown below. For example, a resin sheet for foam molding is produced by extruding a resin composition using an extruder such as a single-screw extruder or a twin-screw extruder. Alternatively, an unfoamed resin molded body is produced by uniformly kneading a resin composition using a kneader equipped with blades such as rollers, cams, kneaders, or Banbarri types, and then pressing it to a predetermined thickness using a hot plate press or the like. The resulting unfoamed resin molded body is placed in a high-pressure vessel, and high-pressure inert gas (such as supercritical carbon dioxide) is injected to impregnate the unfoamed resin molded body with the inert gas. Once sufficient impregnation with the inert gas has occurred, the pressure is released (usually to atmospheric pressure) to generate bubble nuclei in the resin. The bubble nuclei may be allowed to grow at room temperature, but in some cases they may be grown by heating. As for heating methods, known and conventional methods such as water baths, oil baths, hot rolls, hot air ovens, far-infrared radiation, near-infrared radiation, and microwaves can be used. After growing bubbles in this manner, the foam can be obtained by rapidly cooling it with cold water or the like to fix its shape. The unfoamed resin molded body used for foaming is not limited to a sheet; various shapes can be used depending on the application. Furthermore, the unfoamed resin molded body can be manufactured using other molding methods such as injection molding, in addition to extrusion molding and press molding.

[0083] An example of a continuous foam manufacturing method is shown below. For example, a kneading and impregnation step is performed in which a resin composition is kneaded using an extruder such as a single-screw extruder or twin-screw extruder while a high-pressure gas (especially an inert gas, and even carbon dioxide) is injected (introduced) to sufficiently impregnate the resin composition with the high-pressure gas. A molding and depressurization step is performed in which the pressure is released (usually to atmospheric pressure) by pushing the resin composition through a die provided at the tip of the extruder, and molding and foaming are performed simultaneously. In addition, when foam molding is performed in a continuous method, a heating step may be provided as needed to grow bubbles by heating. After growing bubbles in this way, the shape may be fixed by rapidly cooling with cold water or the like as needed. Furthermore, the introduction of high-pressure gas may be performed continuously or discontinuously. Furthermore, in the kneading and impregnation step and the molding and depressurization step, for example, an extruder or injection molding machine may be used. Any appropriate method for heating when growing bubble nuclei can be a water bath, oil bath, hot roll, hot air oven, far-infrared radiation, near-infrared radiation, microwaves, etc. Any suitable shape can be adopted for the foam. Examples of such shapes include sheet-like, prismatic, cylindrical, and irregularly shaped forms.

[0084] The amount of gas mixed when foam molding the resin composition is preferably 2% to 10% by weight, more preferably 2.5% to 8% by weight, and even more preferably 3% to 6% by weight, relative to the total amount of the resin composition, in order to obtain a highly foamed resin foam.

[0085] The pressure used when impregnating the resin composition with an inert gas can be appropriately selected considering ease of operation and other factors. Such a pressure is preferably 6 MPa or higher (e.g., 6 MPa to 100 MPa), and more preferably 8 MPa or higher (e.g., 8 MPa to 50 MPa). When using supercritical carbon dioxide, the pressure is preferably 7.4 MPa or higher from the viewpoint of maintaining the supercritical state of carbon dioxide. If the pressure is lower than 6 MPa, bubble growth during foaming is significant, and the bubble diameter may become too large, making it impossible to obtain a desirable average cell diameter (average bubble diameter). This is because at lower pressures, the amount of gas impregnated is relatively less compared to high pressures, the bubble nucleation rate decreases, and the number of bubble nuclei formed decreases, so the amount of gas per bubble increases, and the bubble diameter becomes extremely large. In addition, in the pressure range below 6 MPa, even a slight change in impregnation pressure can greatly change the bubble diameter and bubble density, making it difficult to control the bubble diameter and bubble density.

[0086] The temperature during the gas impregnation process varies depending on the type of inert gas used and the components in the resin composition, and can be selected within a wide range. Considering ease of operation, the temperature is preferably 10°C to 350°C. When impregnating an unfoamed molded body with an inert gas, the impregnation temperature in a batch process is preferably 10°C to 250°C, and more preferably 40°C to 230°C. Furthermore, when extruding a gas-impregnated molten polymer to simultaneously perform foaming and molding, the impregnation temperature in a continuous process is preferably 60°C to 350°C. When carbon dioxide is used as the inert gas, the impregnation temperature is preferably 32°C or higher, and more preferably 40°C or higher, in order to maintain a supercritical state.

[0087] In the depressurization process, the depressurization rate is preferably 5 MPa / sec to 300 MPa / sec in order to obtain uniform fine bubbles.

[0088] The heating temperature in the heating process is preferably 40°C to 250°C, and more preferably 60°C to 250°C.

[0089] In one embodiment, after obtaining a foamed structure through a predetermined process (for example, after obtaining a resin foam by the method of <Embodiment 1> or <Embodiment 2>), the foamed structure is thinned, and then roll-rolled to obtain a resin foam. By going through such a process, a resin foam with an appropriately adjusted aspect ratio can be obtained. Furthermore, a resin foam with a thin thickness (for example, 0.2 mm or less) can be obtained. The above-mentioned roll-rolling may also form the above-mentioned heat-melted layer.

[0090] The foam structure can be thinned using any suitable slicer. The thickness of the foam structure after thinning is preferably 0.01 mm or more, more preferably 0.05 mm or more, even more preferably 0.1 mm or more, and particularly preferably 0.15 mm or more. The upper limit of the thickness of the foam structure after thinning is preferably 3 mm or less, more preferably 2 mm or less, even more preferably 1.5 mm or less, even more preferably 1 mm or less, even more preferably 0.8 mm or less, and particularly preferably 0.5 mm or less. Within this range, the number of air bubbles in the resin foam is particularly well-adjusted, making it less likely to collapse during punching, and thus a foam member with particularly excellent punching processability can be obtained.

[0091] Preferably, the rolls used in the roll rolling process are heated rolls. The temperature of the rolls is preferably 150°C to 250°C, and more preferably 160°C to 230°C.

[0092] The rolling ratio of the foam structure (thickness after rolling / thickness before rolling × 100) is preferably 80% or less, more preferably 10% to 80%, even more preferably 20% to 75%, and particularly preferably 30% to 75%. Within this range, a resin foam with an appropriately adjusted aspect ratio can be obtained.

[0093] C. Adhesive body As described above, the total amount of toluene and ethyl acetate outgassed from the adhesive is 8.0 μg / g or less. Preferably, the total amount of toluene and ethyl acetate outgassed from the adhesive is 5.0 μg / g or less, and more preferably 2.0 μg / g or less. Within this range, the above effect becomes significant.

[0094] The thickness of the adhesive is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 20 μm or more. The upper limit of the thickness of the adhesive is preferably 500 μm or less, more preferably 300 μm or less, even more preferably 100 μm or less, and particularly preferably 50 μm or less.

[0095] C-1.Adhesive layer As described above, the thickness of the adhesive layer is 50 μm or less. Preferably, the thickness of the adhesive layer is 1 μm or more, more preferably 2 μm or more, even more preferably 3 μm or more, and particularly preferably 5 μm or more. The upper limit of the single-layer thickness of the adhesive layer is preferably 40 μm or less, even more preferably 30 μm or less, even more preferably 20 μm or less, and particularly preferably 18 μm or less. The foamed material of the present invention is suitable for use in areas with narrow clearances. Furthermore, a foamed material with excellent cleanliness and punchability can be obtained.

[0096] The storage modulus of the above adhesive layer at 25°C is preferably 3.0 × 10⁻⁶. 4 Pa~2.0×10 5 Pa is preferably 4.5 × 10 4 Pa~1.2×10 5 Pa is more like 5.0 × 10 4 Pa~8.0×10 4 Pa is particularly preferred, and 5.0 × 10 4 Pa~6.0×10 4 It is Pa.

[0097] The adhesive layer contains any suitable adhesive, provided that the effects of the present invention are obtained. Furthermore, it is preferable that the adhesive layer is formed from a material that does not contain organic solvents. Therefore, it is preferable that the adhesive does not contain organic solvents.

[0098] In one embodiment, the adhesive layer comprises a water-dispersible adhesive. In one embodiment, the water-dispersible adhesive comprises a water-dispersible polymer. Using a water-dispersible adhesive makes it possible to obtain a foamed material with low outgassing and excellent cleanliness. In one embodiment, the water-dispersible adhesive further comprises polyacrylic acid. Adding polyacrylic acid makes it possible to obtain a foamed material with excellent water resistance and impact resistance. The water-dispersible adhesive is advantageous in that it has excellent anchoring properties with a substrate (described later) made of polyethylene terephthalate and excellent coatability.

[0099] (Water-dispersible polymer) Examples of the above-mentioned water-dispersible polymers include water-dispersible acrylic polymers, water-dispersible urethane polymers, water-dispersible polyaniline polymers, and water-dispersible polyester polymers. Preferably, water-dispersible acrylic polymers are used. Water-dispersible adhesives containing water-dispersible acrylic polymers are advantageous in that they have excellent anchoring properties with a substrate made of polyethylene terephthalate (described later) and excellent coatability.

[0100] A water-dispersible acrylic polymer may be a polymer of a monomer composition containing an alkyl (meth)acrylate. (Meth)acrylic acid is defined as acrylic acid and / or methacrylic acid.

[0101] Examples of alkyl (meth)acrylates include alkyl (meth)acrylates having a linear or branched alkyl group with 1 to 20 (preferably 1 to 12) carbon atoms. Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, iso-octyl (meth)acrylate Examples include (meth)acrylates such as methyl acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridodecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadicyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, methyl acrylate and 2-ethylhexyl acrylate are preferred. Alkyl (meth)acrylates may be used individually or in combination of two or more.

[0102] In one embodiment, methyl acrylate and an alkyl acrylate having an alkyl group with 2 to 8 carbon atoms are used in combination. Preferably, methyl acrylate and 2-ethylhexyl acrylate can be used in combination.

[0103] In the water-dispersible acrylic polymer, the proportion of constituent units derived from alkyl (meth)acrylate is, for example, 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more. The proportion of constituent units derived from alkyl (meth)acrylate is, for example, 99.5% by weight or less, preferably 99% by weight or less.

[0104] Water-dispersible acrylic polymers may contain monomer-derived structural units copolymerizable with alkyl (meth)acrylate esters. Examples of such structural units include structural units derived from one or more functional group-containing vinyl monomers. Functional group-containing vinyl monomers are useful for modifying acrylic polymers, such as ensuring cohesive strength and introducing crosslinking points into the acrylic polymer.

[0105] Examples of functional group-containing vinyl monomers include carboxyl group-containing vinyl monomers, acid anhydride vinyl monomers, hydroxyl group-containing vinyl monomers, sulfo group-containing vinyl monomers, phosphate group-containing vinyl monomers, cyano group-containing vinyl monomers, and glycidyl group-containing vinyl monomers.

[0106] Examples of carboxyl group-containing vinyl monomers include acrylic acid, methacrylic acid, 2-carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Among these, acrylic acid or methacrylic acid are preferred. Using such monomers, an adhesive with excellent tackiness and mechanical stability of emulsion particles can be obtained.

[0107] Examples of acid anhydride vinyl monomers include maleic anhydride and itaconic anhydride.

[0108] Examples of hydroxyl group-containing vinyl monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0109] Examples of sulfo group-containing vinyl monomers include styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid.

[0110] Examples of phosphate-containing vinyl monomers include 2-hydroxyethyl acryloyl phosphate.

[0111] Examples of cyano group-containing vinyl monomers include acrylonitrile and methacrylonitrile.

[0112] Examples of vinyl monomers containing a glycidyl group include glycidyl (meth)acrylate and 2-ethylglycidyl ether (meth)acrylate.

[0113] Preferred examples of functional group-containing vinyl monomers include carboxyl group-containing vinyl monomers.

[0114] In the water-dispersible acrylic polymer, the proportion of constituent units derived from functional group-containing vinyl monomers is, for example, 0.5% by weight or more, preferably 1.0% by weight or more, and more preferably 1.5% by weight or more. The proportion of constituent units derived from functional group-containing vinyl monomers is, for example, 30% by weight or less, preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less.

[0115] Water-dispersible acrylic polymers can be obtained, for example, by emulsion polymerization of the above-mentioned monomer composition. In emulsion polymerization, for example, first, a mixture containing monomer, emulsifier, and water is stirred to prepare a monomer emulsion. Next, a polymerization initiator is added to the monomer emulsion to start the polymerization reaction. A chain transfer agent may be used in this polymerization reaction to adjust the molecular weight of the acrylic polymer. Additives such as coupling agents and preservatives can also be used. The polymerization method may be dropwise polymerization or batch polymerization. The polymerization time is, for example, 0.5 hours or more, or for example, 10 hours or less. The polymerization temperature is, for example, 50°C or more, or for example, 80°C or less. By emulsion polymerization, water-dispersible acrylic polymers are prepared as an aqueous dispersion, specifically, an aqueous dispersion (emulsion) in which water-dispersible acrylic polymer is dispersed in water. In other words, the aqueous dispersion contains water-dispersible polymer and water.

[0116] Examples of emulsifiers include anionic emulsifiers, nonionic emulsifiers, and radical polymerizable emulsifiers (reactive emulsifiers).

[0117] Examples of anionic emulsifiers include sodium polyoxyethylene lauryl sulfate, sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene alkyl ether sulfate, ammonium polyoxyethylene alkylphenyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, and sodium polyoxyethylene alkyl sulfosuccinate.

[0118] Examples of nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, and polyoxyethylene polyoxypropylene block polymers.

[0119] Examples of radically polymerizable emulsifiers (reactive emulsifiers) include emulsifiers obtained by introducing radically polymerizable functional groups such as vinyl groups, propenyl groups, isopropenyl groups, vinyl ether groups, and allyl ether groups into the above-mentioned anionic emulsifiers and nonionic emulsifiers. Specifically, ammonium-α-sulfonato-ω-1-(allyloxymethyl)alkyloxypolyoxyethylene is an example. When a reactive emulsifier is used, the acrylic polymer, which is a water-dispersible polymer obtained by emulsion polymerization, contains monomer units derived from the reactive emulsifier.

[0120] The proportion of emulsifier added is, for example, 0.2 to 10 parts by weight per 100 parts by weight of total monomer.

[0121] Examples of polymerization initiators include azo polymerization initiators and peroxide polymerization initiators.

[0122] Examples of azo polymerization initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis{2-[N-(2-carboxyethyl)amidino]propane}n hydrate, and 2,2'-azobis(N,N'-dimethyleneisobutylamidine).

[0123] Examples of peroxide-based polymerization initiators include benzoyl peroxide, t-butyl hydroperoxide, and hydrogen oxide.

[0124] Preferably, the polymerization initiator is an azo polymerization initiator, and more preferably, 2,2'-azobis{2-[N-(2-carboxyethyl)amidino]propane}n hydrate.

[0125] The mixing ratio of the polymerization initiator is, for example, 0.01 to 2 parts by weight per 100 parts by weight of the total amount of monomer.

[0126] Examples of chain transfer agents include glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, t-lauryl mercaptan, t-dodecanethiol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol, with t-dodecanethiol being preferred.

[0127] The proportion of the chain transfer agent is, for example, 0.001 to 0.5 parts by weight per 100 parts by weight of the total amount of monomer.

[0128] The weight-average molecular weight (Mw) of the water-dispersible acrylic polymer is, for example, 100,000 or more, preferably 300,000 or more, and also, for example, 5,000,000 or less, preferably 3,000,000 or less. In this specification, the weight-average molecular weight is calculated on a polystyrene basis by measuring it by gel permeation chromatography (GPC).

[0129] (Polyacrylic acid) The blending ratio of the polyacrylic acid is preferably 0.1 to 7 parts by weight, more preferably 0.15 to 5 parts by weight, more preferably 2.5 to 5 parts by weight, and particularly preferably 3.5 to 5 parts by weight, per 100 parts by weight of the water-dispersible polymer. Within this range, the impact resistance of the adhesive layer can be improved. Furthermore, an adhesive layer with excellent tackiness can be formed.

[0130] The weight-average molecular weight of polyacrylic acid is, for example, 50,000 or more, preferably 100,000 or more, and more preferably 150,000 or more. Alternatively, it may be 300,000 or less, and preferably 250,000 or less.

[0131] (Additives) The above-mentioned water-dispersible adhesive may further contain any suitable additives. Examples of additives include leveling agents, tackifiers, release agents, silane coupling agents, thickeners, crosslinking agents (e.g., 3-methacryloxypropyltrimethoxysilane), fillers, antioxidants, surfactants, and antistatic agents.

[0132] In one embodiment, the water-dispersible adhesive further comprises a leveling agent. Adding the leveling agent yields a water-dispersible adhesive with excellent coatability and suitability for substrates made of polyethylene terephthalate (described later). Furthermore, using such a water-dispersible adhesive allows for the formation of an adhesive layer with excellent impact resistance. Examples of leveling agents include "Surfinol 420" (acetylene glycol ethylene oxide-based surfactant, manufactured by Nisshin Chemical Industry Co., Ltd.), "Perex OT-P" (sodium dialkyl sulfosuccinate, manufactured by Kao Corporation), "Neocol P" (sodium dialkyl sulfosuccinate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), "Nopco Wet 50" (sulfonic acid-based anionic surfactant, manufactured by Sunnopco Co., Ltd.), "SN Wet 126" (modified silicone / special polyether-based surfactant, manufactured by Sunnopco Co., Ltd.), "SN Wet FST2" (nonionic humectant of polyoxyalkyleneamine, manufactured by Sunnopco Co., Ltd.), "SN Wet S" (nonionic humectant of polyoxyalkyleneamine ether, manufactured by Sunnopco Co., Ltd.), and "SN Wet 125" (modified silicone-based surfactant, manufactured by Sunnopco Co., Ltd.). Leveling agents can be used alone or in combination of two or more types.

[0133] In one embodiment, sodium dialkylsulfosuccinate is used as the leveling agent. The number of carbon atoms in sodium dialkylsulfosuccinate is, for example, 4 or more, preferably 6 or more, and more preferably 8 or more. The lower limit of the number of carbon atoms is, for example, 20 or less, preferably 13 or less, and more preferably 10 or less.

[0134] The blending ratio of the leveling agent is, for example, 1 part by weight or more, preferably 1.5 parts by weight or more, and also, for example, 3.5 parts by weight or less, and preferably 2.5 parts by weight or less, per 100 parts by weight of the water-dispersible polymer. Alternatively, the blending ratio of the leveling agent is, for example, 10 parts by weight or more, and also, for example, 500 parts by weight or less, per 100 parts by weight of polyacrylic acid.

[0135] Examples of the tackifiers mentioned above include various tackifier resins such as rosin resins, rosin derivative resins, petroleum resins, terpene resins, phenolic resins, and ketone resins, with rosin resins and terpene resins being preferred, and terpene resins being more preferred. The content of the tackifier is, for example, 5 parts by weight or more, preferably 15 parts by weight or more, more preferably 25 parts by weight or more, even more preferably 33 parts by weight or more, and also, for example, 50 parts by weight or less, preferably 45 parts by weight or less, and more preferably 38 parts by weight or less, per 100 parts by weight of the water-dispersible polymer.

[0136] C-2. Base material As the base material, a base material formed from any suitable resin can be used. Examples of resins constituting the base material include polyester resins, polyolefin resins, polyvinyl chloride, polyimide resins, and polyamide resins. Among these, polyester resins are preferred, and polyethylene terephthalate is more preferred. Using a base material formed from polyethylene terephthalate makes it possible to obtain a remarkably thin foamed member. Furthermore, it has high tensile strength and is not easily cut, making it advantageous in terms of ease of processing. In addition, because it has a high melting point, the dimensional change rate at high temperatures is small, which is advantageous in that it can be used in various environments. By using the above-mentioned water-dispersible adhesive, it is possible to preferably use a base material composed of polyethylene terephthalate, and as a result, a remarkably thin foamed member with excellent cleanliness (for example, low outgassing) can be obtained.

[0137] The breaking strength of the above-mentioned substrate at 23°C is preferably 200 MPa to 500 MPa, more preferably 260 MPa to 420 MPa, even more preferably 300 MPa to 380 MPa, and particularly preferably 320 MPa to 360 MPa. Within this range, a substrate with appropriate strength can be obtained. Such a substrate has excellent die-cutting processability, and tearing, dust generation, and uncut pieces are prevented during die-cutting. The breaking strength is measured using a tensile testing machine at 23°C and 50% RH with a chuck distance of 120 mm and a tensile speed of 50 mm / min, using a test piece (substrate) cut to a size of 10 mm in width and 150 mm in length. The breaking strength of the above-mentioned substrate may be the breaking strength in the processing flow direction when forming the substrate into a film.

[0138] When the above adhesive material is provided with a base material, the breaking strength of the adhesive material at 23°C is preferably 200 MPa to 500 MPa, more preferably 260 MPa to 420 MPa, even more preferably 300 MPa to 380 MPa, and particularly preferably 320 MPa to 360 MPa.

[0139] The dimensional change rate when the above substrate is left at 150°C for 30 minutes is preferably 1% to 5%, more preferably 1% to 3%, even more preferably 1.2% to 2.8%, and particularly preferably 1.5% to 2.5%. Within this range, a foamed material with small dimensional changes can be obtained even in high-temperature environments. Such a substrate can maintain its shape in various environments, and variations in processed dimensions are suppressed. The above dimensional change rate is the dimensional change rate in the direction with the largest change rate among the dimensional change rates in each direction (e.g., width direction, length direction, thickness direction, etc.) of a test piece with a width of 100 mm, a length of 100 mm, and a thickness of 1 to 25 μm. For example, a dimensional change rate of 10% or less means that the dimensional change rates in the width direction, length direction, and thickness direction of the above test piece are all 10% or less. The dimensional change rate (%) can be calculated from the following. Dimensional change rate (%) = (L0 - L1) / L0 × 100 L0: Dimensions of the initial test specimen (blank value) L1: Dimensions of the test specimen after being left at 150℃ for 30 minutes.

[0140] When the above-mentioned adhesive material is provided with a base material, the dimensional change rate when the adhesive material is left at 150°C for 30 minutes is preferably 1% to 5%, more preferably 1% to 3%, even more preferably 1.2% to 2.8%, and particularly preferably 1.5% to 2.5%.

[0141] The total light transmittance of the substrate (JIS K 7375-2008) is, for example, 80% or more, preferably 85% or more.

[0142] The thickness of the base material is preferably 1 μm or more, more preferably 2 μm or more. The upper limit of the base material thickness is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 10 μm or less, and particularly preferably 7 μm or less. Within this range, it is possible to obtain a remarkably thin foamed material. Furthermore, it has high tensile strength and is not easily cut, which is advantageous in terms of die-cutting.

[0143] C-3. Easy adhesion layer In one embodiment, the adhesive may further comprise an easy-adhesion layer between the substrate and the adhesive layer. The easy-adhesion layer is formed from an easy-adhesion composition, which is an adhesive composition.

[0144] In one embodiment, the easy-adhesion composition comprises an oxazoline group-containing polyester polymer. In one embodiment, the oxazoline group-containing polyester polymer comprises polyester-derived structural units and oxazoline-derived structural units.

[0145] The above polyester is a polymer in which ester bonds, formed by the dehydration condensation of a polycarboxylic acid and a polyol, link them together. Examples of the polycarboxylic acid include phthalic acid (terephthalic acid, isophthalic acid) and naphthalenedicarboxylic acid. Phthalic acid is preferred. Examples of the polyol include aliphatic glycols having 2 to 8 carbon atoms.

[0146] Oxazoline group-containing polyester polymers can be obtained, for example, by reacting a water-soluble copolymer polyester (polyester component) obtained in accordance with the method described in Japanese Patent Publication No. 06-293838 with an oxazoline-based reactive polymer (oxazoline component).

[0147] The water contact angle of the easily adhering layer is, for example, 60° or more, and for example, 75° or less, preferably. 71° or less, more preferably 68° or less, and even more preferably 65° or less.

[0148] The thickness of the easy-adhesion layer is, for example, 50 nm or less, more preferably 45 nm or less, and for example, 1 nm or more, preferably 10 nm or more.

[0149] The foamed material described above can be manufactured by any suitable method. For example, the foamed material can be manufactured by laminating a resin foam with an adhesive layer (or adhesive material (adhesive sheet)). [Examples]

[0150] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way to these examples. The test and evaluation methods in the examples are as follows. When "parts" is written, it means "parts by weight" unless otherwise specified, and when "%" is written, it means "percent by weight" unless otherwise specified.

[0151] <Evaluation Method> (1) Apparent density The density (apparent density) of the resin foam was calculated as follows. The resin foam obtained in the examples and comparative examples was punched out to a size of 20 mm x 20 mm to make test specimens, and the dimensions of the test specimens were measured with calipers. Next, the weight of the test specimens was measured with an electronic balance. Then, the density was calculated using the following formula. Apparent density (g / cm³) 3 ) = Weight of test specimen / Volume of test specimen (2) 50% compression load The measurement was performed in accordance with the method for measuring the compression hardness of resin foams described in JIS K 6767. Specifically, the resin foam obtained in the examples and comparative examples was cut into 30mm x 30mm pieces to serve as test specimens, and the stress (N) when compressed at a compression speed of 10mm / min until the compression ratio reached 50% was measured per unit area (1cm²). 2 Converted to a unit per inch, 50% compressive load (N / cm²) 2 ) (3) Average bubble diameter (average cell diameter), coefficient of variation of bubble diameter (cell diameter) The resin foam was cut perpendicular to its main surface (thickness direction) using a razor blade. A digital microscope (product name "VHX-500", manufactured by Keyence Corporation) was used as a measuring instrument to capture images of the cut surface of the resin foam. The number-mean bubble diameter (average cell diameter) (μm) was determined by image analysis using the instrument's analysis software. The number of bubbles in the magnified image captured was approximately 400. The standard deviation was calculated from all the cell diameter data, and the coefficient of variation was calculated using the following formula. Coefficient of variation = Standard deviation / Average bubble diameter (Average cell diameter) (4) Bubble rate (cell rate) Measurements were performed under conditions of 23°C and 50% humidity. The resin foam obtained in the examples and comparative examples was punched out using a 100mm x 100mm punching die (two processing blades (product name "NCA07", thickness 0.5mm, blade tip angle 45°, manufactured by Nakayama Co., Ltd.)), and the dimensions of the punched samples were measured. The thickness was also measured using a 1 / 100 dial gauge with a measuring terminal diameter (φ) of 20mm. From these values, the volume of the resin foam obtained in the examples and comparative examples was calculated. Next, the weight of the resin foam obtained in the examples and comparative examples was measured using a balance scale with a minimum scale of 0.01g or more. From these values, the bubble rate (cell rate) of the resin foam obtained in the examples and comparative examples was calculated. (5) Number of bubbles The resin foam was cut perpendicular to the main surface (thickness direction) using a razor blade. A digital microscope (product name "VHX-500", manufactured by Keyence Corporation) was used as a measuring instrument to capture images of the cut surface of the resin foam, and the image was analyzed using the analysis software of the same instrument to determine the area per unit area [mm²]. 2 The number of bubbles per unit was measured. (6) Total emissions of toluene outgassing and ethyl acetate outgassing Apply adhesive material (adhesive sheet / tape) to a 5cm sample. 2 The sample was cut and sealed in a 20 mL headspace vial. The vial containing the sample was heated at 80°C for 30 minutes using a headspace sampler (Shimadzu HS-20). After heating, 1 mL of the gas phase portion was quantitatively analyzed using a GC (Shimadzu QP2010 Ultra) to measure the total amount of toluene and ethyl acetate outgassed. (7) Crimping area ratio The adhesive materials (adhesive sheets and tapes) and foam materials (40mm x 40mm each) obtained in the examples and comparative examples were pressed together by passing a 2kg roller back and forth once. After 30 minutes, the materials were observed using a digital microscope (product name "VHX-500", manufactured by Keyence Corporation) as a measuring instrument. The images were binarized using image processing software (WinROOF, manufactured by Mitani Corporation), and the pressure area ratio was calculated using the following formula. Crimping area ratio % = (Crimping area / Total area) × 100 Criteria for evaluating anchoring ability: Excellent (◎): 90%~100%; Good (〇): 60% or more and less than 90%; Acceptable (△): 20% or more and less than 60%; Poor (×): 0% or more and less than 20% (8) Percentage change in thickness during crimping [%] The adhesive materials (adhesive sheets and tapes) and foam materials (40mm x 40mm each) obtained in the examples and comparative examples were bonded together and pressed down with a 5kg roller, passing it back and forth three times. Next, the thickness was measured after 30 minutes, and the thickness change rate was calculated using the following formula. The percentage change in thickness during crimping [%] = (thickness before crimping - thickness after crimping) / (thickness before crimping) × 100 (9) Storage modulus of the adhesive layer (25°C) The dynamic viscoelasticity was determined by performing dynamic viscoelasticity measurements under the following conditions using the Rheometric ARES dynamic viscoelasticity analyzer. For the measurement sample, a portion of the adhesive layer was pressed to a thickness of 2 mm. ·Equipment: ARES (Advance) manufactured by Rheometric Scientific dRheometric Expansion System) • Frequency: 1Hz ·Temperature: -60~150℃ • Heating rate: 5°C / min • Transformation mode: Twist • Shape: Parallel plate (7.9mmφ) (10) Punching processability (thickness recovery rate after processing) Foam material was punched out to a size of 10mm x 10mm using a mold (two cutting blades (product name "NCA07", thickness 0.7mm, cutting edge angle 43°, distance between the two cutting blades 10mm, manufactured by Nakayama Co., Ltd.)) in the MD direction (flow direction) and TD direction (direction perpendicular to the flow direction). The cross-section with the greater thickness change between the MD and TD directions was observed with a microscope (product name "VHX-2000", manufactured by Keyence Corporation). The thickness recovery rate after processing was measured using the thickness of the edge measured from the image and the thickness before punching, using the following formula. A larger thickness recovery rate indicates less shape change due to punching and superior punching processability. Thickness recovery rate after processing (%) = 100 × (1 - (thickness before punching - thickness at the edge) / thickness before punching) (11) Thickness recovery rate (instantaneous recovery rate) The foam material contains 1000 g / cm³ 2 The foam material was subjected to a load and maintained for 120 seconds. The compression was then released, and the thickness of the foam material 0.5 seconds after the release (thickness 0.5 seconds after the release of compression) was measured. The thickness recovery rate (instantaneous recovery rate) was calculated from the "thickness 0.5 seconds after the release of compression" and the thickness of the foam material before the load was applied (initial thickness) using the following formula. Thickness recovery rate (%) = {(Thickness 0.5 seconds after decompression) / (Initial thickness)} × 100

[0152] [Manufacturing Example 1] <Preparation of adhesive sheets (double-sided adhesive sheet A, adhesive sheet A')> In a reaction vessel equipped with a thermometer, stirrer, nitrogen inlet tube, and reflux condenser, 0.07 parts by weight of emulsifier and 61.1 parts by weight of distilled water were added, and the mixture was purged with nitrogen at room temperature (25°C) for 1 hour while stirring. Then, 0.1 parts by weight of polymerization initiator was added, and the temperature was raised to 60°C. Next, 85 parts by weight of 2-ethylhexyl acrylate (2EHA), 13 parts by weight of methyl acrylate (MA), 1.25 parts by weight of acrylic acid (AA), 0.75 parts by weight of methacrylic acid (MAA), 0.025 parts by weight of t-dodecanethiol (chain transfer agent), 0.02 parts by weight of crosslinking agent, and 1.93 parts by weight of emulsifier were emulsified with 28 parts by weight of distilled water, and polymerized dropwise at 60°C for 4 hours. After that, the mixture was cooled to room temperature, and the pH was adjusted to 6 using 10% aqueous ammonia as a pH adjuster. This synthesized a water-dispersible acrylic polymer. To 100 parts by weight of water-dispersible acrylic polymer solids, 30 parts by weight of tackifier, 3 parts by weight of thickener, and 2 parts by weight of leveling agent were added. This mixture was then diluted and neutralized with distilled water and 10% aqueous ammonia to prepare water-dispersible adhesive composition A (solids concentration 25% by mass). Water-dispersible adhesive composition A was applied to the surface of a release film to a thickness of 13 μm and dried to form (arrange) an adhesive layer. This resulted in a substrate-less adhesive sheet A'. Next, an easily adhesive layer containing an oxazoline group-containing polyester polymer (with a peak intensity ratio of 11 between the peak intensity derived from the oxazoline component and the peak intensity derived from the polyester component, as measured by TOFSIMS) was applied to both sides of a polyester film (product name "K880-4.5W," manufactured by Mitsubishi Chemical Polyester Co., Ltd.; thickness: 4 μm). Furthermore, the adhesive sheet A' was transferred to both sides of the polyester film with the easy-adhesion layer obtained above. This produced a double-sided adhesive sheet A.

[0153] [Manufacturing Example 2] <Creating an adhesive sheet (double-sided adhesive tape B)> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, dropping device, and nitrogen inlet tube, 35 parts by weight of deionized water were added and stirred at 60°C for more than 1 hour while introducing nitrogen gas. To this, 0.1 parts by weight of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate was added as a polymerization initiator to prepare the reaction solution. As monomer raw materials, 90 parts by weight of n-butyl acrylate, 10 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of acrylic acid, 2 parts by weight of sodium polyoxyethylene lauryl sulfate (emulsifier), and 0.05 parts by weight of dodecanethiol (chain transfer agent) were added to 40 parts by weight of ion-exchanged water and emulsified to obtain a monomer raw material emulsion. The monomer raw material emulsion was gradually added dropwise to the reaction solution maintained at 60°C over 4 hours to induce emulsion polymerization. After the addition of the monomer raw materials was complete, the mixture was stirred at 60°C for another 2 hours, and then the heating was stopped. Next, 0.1 parts by weight of ascorbic acid and 0.1 parts by weight of 35% hydrogen peroxide (additional polymerization initiator) were added to 100 parts by weight of monomer to perform a redox treatment. After cooling to room temperature, 10% aqueous ammonia was added to adjust the pH to 7 to obtain an acrylic polymer emulsion (water-dispersible acrylic polymer). To the acrylic polymer emulsion, 30 parts by weight of a tackifying resin emulsion (in terms of solid content) per 100 parts by weight of the acrylic polymer contained in the emulsion was added to obtain a water-dispersible adhesive composition. Next, a release liner substrate was prepared in which a 25 μm thick PE layer was laminated to one side of fine paper. A mixture of a non-migratory thermosetting solvent-free silicone release agent and a curing catalyst was applied to the PE layer of this substrate. This was held at 120°C for 1 minute to dry and harden, obtaining a release liner. The above water-dispersible adhesive composition was applied to the release layer of the obtained release liner to a thickness of 55 μm to form an adhesive layer. Two of these were prepared and transferred to each side of a nonwoven fabric substrate (Daifuku Paper Co., Ltd., product name "SP Base Paper-14", pulp-based nonwoven fabric with a thickness of 42 μm) to obtain a double-sided adhesive sheet B.

[0154] [Manufacturing Example 3] <Double-sided adhesive tape C creation> 65 parts by weight of n-butyl acrylate, 35 parts by weight of 2-ethylhexyl acrylate, 3 parts by weight of acrylic acid, 0.05 parts by weight of 4-hydroxybutyl acrylate, and 0.08 parts by weight of AIBN (azobisisobutyronitrile) as a polymerization initiator were added to toluene solvent. Then, solution polymerization was carried out at 63°C for 8 hours to obtain an acrylic polymer solution. The acrylic acid content was 2.9% by weight relative to the total monomer components. To the prepared acrylic polymer solution, 30 parts by weight of polymerized rosin ester (softening point: 128°C, acid value: 12 mg KOH / g) and 2 parts by weight of isocyanate crosslinking agent were added to prepare acrylic adhesive composition c. Adhesive composition c was applied to the surface of the release film to a thickness of 13 μm, dried, and an adhesive layer was formed (placed). This adhesive layer was transferred to both sides of a polyester film (product name "K880-4.5W," manufactured by Mitsubishi Chemical Polyester Co., Ltd.; thickness: 4 μm). This produced a double-sided adhesive sheet C.

[0155] [Example 1] 35 parts by weight of polypropylene (MFR: 0.4 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 108,000, molecular weight distribution: 4.93), 30 parts by weight of polyolefin elastomer A (melt flow rate (MFR): 15 g / 10 min), 30 parts by weight of polyolefin elastomer B (melt flow rate (MFR): 2.2 g / 10 min), 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into strands, water-cooled, and molded into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) under an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the material was cooled to a temperature suitable for foaming, extruded from the die, and sliced ​​to a thickness of 1.0 mm to obtain a sheet-like resin foam a. A double-sided adhesive sheet A was bonded to one side of the resin foam a to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0156] [Example 2] 35 parts by weight of polypropylene (MFR: 0.4 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 108,000, molecular weight distribution: 4.93), 42 parts by weight of polyolefin elastomer A (melt flow rate (MFR): 15 g / 10 min), 18 parts by weight of polyolefin elastomer B (melt flow rate (MFR): 2.2 g / 10 min), 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd., then extruded into strands, water-cooled, and formed into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the resin was cooled to a temperature suitable for foaming, extruded from the die, and sliced ​​to a thickness of 1.0 mm to obtain a sheet-like resin foam b. A double-sided adhesive sheet A was bonded to one side of the resin foam b to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0157] [Example 3] 25 parts by weight of polypropylene (MFR: 0.4 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 108,000, molecular weight distribution: 4.93), 10 parts by weight of polypropylene (MFR: 1.1 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%), 42 parts by weight of polyolefin elastomer A (melt flow rate (MFR): 15 g / 10 min), 18 parts by weight of polyolefin elastomer B (melt flow rate (MFR): 2.2 g / 10 min), 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into strands, water-cooled, and molded into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the material was cooled to a temperature suitable for foaming, extruded from the die, and sliced ​​to a thickness of 1.0 mm to obtain a sheet-like resin foam c. A double-sided adhesive sheet A was bonded to one side of the resin foam c to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0158] [Example 4] 45 parts by weight of polypropylene (MFR: 0.5 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 64500, molecular weight distribution: 8.43), 36 parts by weight of polyolefin elastomer A (melt flow rate (MFR): 15 g / 10 min), 14 parts by weight of polyolefin elastomer B (melt flow rate (MFR): 2.2 g / 10 min), 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd., then extruded into strands, water-cooled, and formed into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the resin was cooled to a temperature suitable for foaming, extruded from the die, and sliced ​​to a thickness of 1.0 mm to obtain a sheet-like resin foam d. A double-sided adhesive sheet A was bonded to one side of the resin foam d to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0159] [Example 5] 40 parts by weight of polypropylene (MFR: 0.5 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 64500, molecular weight distribution: 8.43), 38.5 parts by weight of polyolefin elastomer A (melt flow rate (MFR): 15 g / 10 min), 16.5 parts by weight of polyolefin elastomer B (melt flow rate (MFR): 2.2 g / 10 min), 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw mixer manufactured by Japan Steel Works, Ltd., then extruded into strands, water-cooled, and formed into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the mixture was cooled to a temperature suitable for foaming, extruded from the die, and sliced ​​to a thickness of 1.0 mm to obtain a sheet-like resin foam e. A double-sided adhesive sheet A was bonded to one side of the resin foam e to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0160] [Example 6] 40 parts by weight of polypropylene (MFR: 0.5 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 64500, molecular weight distribution: 8.43), 55 parts by weight of polyolefin elastomer A (melt flow rate (MFR): 15 g / 10 min), 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd., then extruded into strands, water-cooled, and molded into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) under an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After sufficiently saturating with carbon dioxide gas, the material was cooled to a temperature suitable for foaming, extruded from the die, and sliced ​​to a thickness of 1.0 mm to obtain a sheet-like resin foam f. A double-sided adhesive sheet A was bonded to one side of the resin foam f to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0161] [Example 7] 30 parts by weight of polypropylene (MFR: 0.5 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 64500, molecular weight distribution: 8.43), 10 parts by weight of polypropylene (MFR: 1.1 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%), 38.5 parts by weight of polyolefin elastomer A (melt flow rate (MFR): 15 g / 10 min), 16.5 parts by weight of polyolefin elastomer B (melt flow rate (MFR): 2.2 g / 10 min), 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into strands, water-cooled, and molded into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) under an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the material was cooled to a temperature suitable for foaming, extruded from the die, and sliced ​​to a thickness of 1.0 mm to obtain a sheet-like resin foam g. A double-sided adhesive sheet A was bonded to one side of the resin foam g to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0162] [Example 8] 45 parts by weight of polypropylene (MFR: 0.4 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 108,000, molecular weight distribution: 4.93), 30 parts by weight of polypropylene (MFR: 1.1 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%), 25 parts by weight of polyolefin elastomer C (melt flow rate (MFR): 6.0 g / 10 min), 100 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd., then extruded into strands, water-cooled, and formed into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the resin was cooled to a temperature suitable for foaming, and then extruded from the die to obtain a sheet-like resin foam. The obtained resin foam was sliced ​​to a thickness of 0.5 mm and rolled to 0.15 mm using a 200°C hot melt roll to form a hot melt layer, thereby obtaining resin foam h. A double-sided adhesive sheet A was bonded to one side of resin foam h to obtain a foamed member. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0163] [Example 9] 45 parts by weight of polypropylene (MFR: 0.4 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 108,000, molecular weight distribution: 4.93), 30 parts by weight of polypropylene (MFR: 1.1 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%), 25 parts by weight of polyolefin elastomer C (melt flow rate (MFR): 6.0 g / 10 min), 120 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd., then extruded into strands, water-cooled, and formed into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the resin was cooled to a temperature suitable for foaming, and then extruded from the die to obtain a sheet-like resin foam. The obtained resin foam was sliced ​​to 0.5 mm and rolled to 0.15 mm using a 200°C hot melt roll to form a hot melt layer to obtain resin foam i. A double-sided adhesive sheet A was bonded to one side of resin foam i to obtain a foamed member. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0164] [Example 10] 45 parts by weight of polypropylene (MFR: 0.4 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%, weight-average molecular weight: 108,000, molecular weight distribution: 4.93), 30 parts by weight of polypropylene (MFR: 1.1 g / 10 min, ethylene content: 0 wt%, propylene content: 100 wt%), 25 parts by weight of polyolefin elastomer C (melt flow rate (MFR): 6.0 g / 10 min), 140 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were mixed at a temperature of 200°C in a twin-screw mixer manufactured by Japan Steel Works, Ltd., then extruded into strands, water-cooled, and formed into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the resin was cooled to a temperature suitable for foaming, and then extruded from the die to obtain a sheet-like resin foam. The obtained resin foam was sliced ​​to 0.5 mmd and rolled to 0.15 mm using a 200°C hot melt roll to form a hot melt layer to obtain resin foam j. A double-sided adhesive sheet A was bonded to one side of resin foam j to obtain a foamed member. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0165] [Example 11] A resin foam a was obtained in the same manner as in Example 1. An adhesive sheet A' was bonded to one side of the resin foam a to obtain a foamed member. The obtained foamed member was subjected to the above evaluation. The results are shown in Table 1.

[0166] [Comparative Example 1] 35 parts by weight of polypropylene (MFR: 0.4 g / 10 min, ethylene content: 0% by weight, propylene content: 100% by weight, weight-average molecular weight: 108,000, molecular weight distribution: 4.93), 60 parts by weight of thermoplastic elastomer composition [a blend of polypropylene (PP) and ethylene / propylene / 5-ethylidene-2-norbornene three-dimensional copolymer (EPT) (crosslinked olefin-based thermoplastic elastomer, TPV), the ratio of polypropylene to ethylene / propylene / 5-ethylidene-2-norbornene three-dimensional copolymer is 25 / 75 by weight, containing 15.0% by weight of carbon black], 10 parts by weight of magnesium hydroxide, 10 parts by weight of carbon, and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works, Ltd. (JSW), extruded into strands, water-cooled, and molded into pellets. These pellets were fed into a single-screw extruder manufactured by Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. The carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After the carbon dioxide gas was sufficiently saturated, the material was cooled to a temperature suitable for foaming, and then extruded from the die to obtain a sheet-like resin foam. The skin layer of the obtained resin foam was removed by slicing, and the material was sliced ​​to a thickness of 1 mm to obtain resin foam k. Double-sided adhesive tape B was attached to one side of resin foam k to obtain a foamed component. The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0167] [Comparative Example 2] A foamed material was obtained by laminating a double-sided adhesive sheet A to one side of a 3.0 mm thick EPDM rubber foam (product number: EE-1000, manufactured by Nitto Denko). The obtained foamed material was subjected to the above evaluation. The results are shown in Table 1.

[0168] [Comparative Example 3] A resin foam k was obtained in the same manner as in Comparative Example 1. A double-sided adhesive tape C was attached to one side of the resin foam k to obtain a foamed member. The obtained foamed member was subjected to the above evaluation. The results are shown in Table 1.

[0169] [Table 1]

[0170] As is clear from the "anchoring ability" evaluation shown in Table 1, the foamed material of the present invention exhibits excellent integration between the resin foam and the adhesive layer. Furthermore, according to the present invention, it is possible to provide a foamed material with low toluene and ethyl acetate outgassing and excellent cleanliness. [Industrial applicability]

[0171] The resin foam of the present invention can be suitably used, for example, as a cushioning material for electronic devices. [Explanation of Symbols]

[0172] 100 Foamed material 110 Resin foam 120 Adhesive 121 Adhesive layer

Claims

1. The device comprises a resin foam and an adhesive disposed on at least one side of the resin foam, The adhesive comprises a base material and an adhesive layer disposed between the base material and the resin foam. The average bubble diameter of the resin foam is 900 μm or less. The resin foam contains a polyolefin resin, The thickness of the adhesive layer is 50 μm or less. The adhesive layer contains a water-dispersible adhesive. In the adhesive, the total amount of toluene outgassing and ethyl acetate outgassing is 8.0 μg / g or less. Foamed material.

2. The foamed member according to claim 1, wherein the adhesive material is an adhesive sheet.

3. The foamed member according to claim 1, wherein the adhesive body comprises the adhesive layer disposed on both sides of the substrate.

4. The foamed member according to claim 1, wherein the base material is made of polyethylene terephthalate.

5. The apparent density of the aforementioned resin foam is 0.03 g / cm³. 3 ~0.4 g / cm 3 The foamed member according to claim 1.

6. The foamed member according to claim 1, wherein the coefficient of variation of the bubble diameter of the resin foam is 0.4 or less.

7. The foamed member according to claim 1, wherein the foamed resin has a bubble rate of 97% or less.

8. The number density of bubbles in the aforementioned resin foam is 50 bubbles / mm². 2 The foamed member according to claim 1.

9. The foamed member according to claim 1, wherein the polyolefin resin is a mixture of a polyolefin other than a polyolefin elastomer and a polyolefin elastomer.

10. The foamed member according to claim 1, wherein the resin foam has a heat-melting layer on one or both sides.

11. The foamed member according to claim 1, wherein another adhesive layer is formed on the surface of the resin foam opposite to the adhesive layer.

Citation Information

Patent Citations

  • Soundproofing plate provided with pressure-bondable pressure-sensitive adhesive layer

    JP1998017831A

  • Adhesive tape

    JP2014185310A

  • Impact absorption material

    JP2015034299A

  • Foam for buffer material and buffer material

    JP2017186504A

  • Foam sheet

    JP2019167483A